THE EXPLOITATION OF AUTHENTICITY IN SPEAKING SIMULATION BY THIRD-YEAR FAST-TRACK STUDENTS - Phan, Ngọc Quỳnh Anh (2020)
For the past few years, there have been a lot of heated debates in the educational forums about students’ lack of opportunities to acquire real language that is used outside classroom. In the context of globalization and integrity, it is more than ever important to have authenticity injected into language learning environment to meet the demand of learners and the society as a whole. As one of the pioneers in foreign language teaching and learning, the Fast-Track group at ULIS, VNU has made an attempt to bridge the gap between classroom knowledge and real world practices by including simulation as an activity in the speaking course for third-year Fast-Track students. To meet the goal of this activity, it is, therefore, necessary that authenticity should go hand in hand with simulation. Continuing this line of research, the purpose of the present study sheds light on the exploitation of authenticity in the second simulation that third-year Fast-Track students conducted in semester two of the academic year. Moreover, the progress in terms of authenticity when compared the second with the first simulation done in semester one is also a focus of this study. In the first place, survey questionnaires were employed to study 26 third-year students in the Fast-Track group.